Comparison of acute physiology and chronic health evaluation II and acute physiology and chronic health evaluation IV to predict intensive care unit mortality - Parajuli, Bashu Dev (Indian J Crit Care Med, 2015)
CONTEXT: Clinical assessment of severity of illness is an essential component of medical practice to predict the outcome of critically ill-patient. Acute Physiology and Chronic Health Evaluation (APACHE) model is one of the widely used scoring systems. AIMS: This study was designed to evaluate the Performance of APACHE II and IV scoring systems in our Intensive Care Unit (ICU). SETTINGS AND DESIGN: A prospective study in 6 bedded ICU, including 76 patients all above 15 years. SUBJECTS AND METHODS: APACHE II and APACHE IV scores were calculated based on the worst values in the first 24 h of admission. All enrolled patients were followed, and outcome was recorded as survivors or nonsurvivors. STATISTICAL ANALYSIS USED: SPSS version 17. RESULTS: The mean APACHE score was significantly higher among nonsurvivors than survivors (P < 0.005). Discrimination for APACHE II and APACHE IV was fair with area under receiver operating characteristic curve of 0.73 and 0.79 respectively. The cut-off point with best Youden index for APACHE II was 17 and for APACHE IV was 85. Above cut-off point, mortality was higher for both models (P < 0.005). Hosmer–Lemeshow Chi-square coefficient test showed better calibration for APACHE II than APACHE IV. A positive correlation was seen between the models with Spearman's correlation coefficient of 0.748 (P < 0.01). CONCLUSIONS: Discrimination was better for APACHE IV than APACHE II model however Calibration was better for APACHE II than APACHE IV model in our study. There was good correlation between the two models observed in our study.